2011
DOI: 10.1371/currents.rrn1255
|View full text |Cite
|
Sign up to set email alerts
|

Modifiers of mutant huntingtin aggregationfunctional conservation of C. elegans-modifiers of polyglutamine aggregation

Abstract: Protein aggregation is a common hallmark of a number of age-related neurodegenerative diseases, including Alzheimer's, Parkinson's, and polyglutamine-expansion disorders such as Huntington's disease, but how aggregation-prone proteins lead to pathology is not known. Using a genome-wide RNAi screen in a C. elegans-model for polyglutamine aggregation, we previously identified 186 genes that suppress aggregation. Using an RNAi screen for human orthologs of these genes, we here present 26 human genes that suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 46 publications
1
17
0
1
Order By: Relevance
“…Both wild-type and mutant Htt co-purify with sev- eral translation-related proteins, co-fractionate with ribosomes, localize to stress granules, and inhibit translation when overexpressed in an in vitro assay. These observations are supported by genetic interaction screens where shRNA-mediated knockdown of proteins involved in protein synthesis enhanced aggregation of a polyglutamine-expanded N-terminal Htt fragment (53), which is in one way or another tied to disease outcome (70). This connection between HD and translation is further supported by the observation that the level of the kinase PKR, an inhibitor of cap-dependent translation, is elevated in HD patient brains (59).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Both wild-type and mutant Htt co-purify with sev- eral translation-related proteins, co-fractionate with ribosomes, localize to stress granules, and inhibit translation when overexpressed in an in vitro assay. These observations are supported by genetic interaction screens where shRNA-mediated knockdown of proteins involved in protein synthesis enhanced aggregation of a polyglutamine-expanded N-terminal Htt fragment (53), which is in one way or another tied to disease outcome (70). This connection between HD and translation is further supported by the observation that the level of the kinase PKR, an inhibitor of cap-dependent translation, is elevated in HD patient brains (59).…”
Section: Discussionmentioning
confidence: 80%
“…4b, compare the upper and lower FLAG blots). Translation factors have a modifying effect on the aggregation and toxicity of N-terminal fragment-based models of mutant Htt toxicity in Caenorhabditis elegans and Saccharomyces cerevisiae (52,53). The differences in sedimentation profiles, mass spectrometry-identified protein associations, and the modifying effect that translation proteins have on mutant Htt toxicity in model systems suggest that mutant Htt may affect translation.…”
Section: ϫ10mentioning
confidence: 99%
“…Tenascin‐R co‐aggregates with APP at nodes of Ranvier on myelinated axons (Xu et al ., 2014). Knockdown of UBA1 or talin‐2 increased aggregation of a polyglutamine array in C. elegans and of transgenic huntingtin (Htt‐Q74‐GFP) in cultured human HEK293 cells (Teuling et al ., 2011). Frame‐shifted misreading of ubiquitin‐B inhibits proteasomes in transgenic mice and phenotypically mimics AD (Irmler et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…We used TRiC reagents to rescue BDNF delivery. Suggesting that using TRiC may have an impact on HD pathogenesis, (i) wtHtt was found to interact with >700 cellular proteins, including CCT1 and CCT8 (57), and (ii) a Caenorhabditis elegans screening assay showed that six of eight CCT subunits suppressed mutant huntingtin aggregation (58). A technical challenge for using TRiC is that the TRiC complex consists of eight CCT subunits; introducing all eight subunits posed a daunting task.…”
Section: Impaired Lysosome Transport In Bachd Cortical Neurons Wasmentioning
confidence: 99%